KOMPARASI KINERJA SAHAM PT UNILEVER INDONESIA TBK SEBELUM DAN PADA SAAT PANDEMI COVID-19 (PERIODE TAHUN 2017-2022) - Didi Rahmat; Sukma Febrianti; Imam Suharto (Jurnal Ekonomi STIEP, 2023)
PT Unilever is one of the leading companies in Indonesia, which has become an attraction to invest in the company. The Covid-19 pandemic caused all business sectors to have a downtrend impact, as did the Unilever company, whose share price fell quite deeply during the pandemic. Using an Independent T-test sample, this study will examine differences in Unilever stock performance before and during the Covid-19 pandemic. The test result shows that there is a significant difference in Unilevers stock performance before and during the Covid-19 pandemic.